Color Stability of Nanofilled and Microhybrid Resin-Based Composites following Exposure to Chlorhexidine Mouthrinses: An In Vitro Study - Mahmood Khosravi; Behnaz Esmaeili; Forough Nikzad; Soraya Khafri (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to evaluate the effects of chlorhexidine mouthrinses on color stability of nanofilled and micro-hybrid resin-based composites. Materials and Methods: In this in-vitro study, 160 disc-shaped specimens (7x2mm) were fabricated of Filtek Z250 and Filtek Z350XT Enamel (A2 shade). The samples of each group were randomly divided into eight subgroups (n=10). The specimens were incubated in artificial saliva at 37˚C for 24 hours. The baseline color values (L*, a*, b*) of each specimen were measured according to CIE LAB system using a reflection spectrophotometer. After baseline color measurements, the control samples were immersed in saliva and the test groups were immersed in Kin (Cosmodent), Vi-One (Rozhin), Epimax (Emad), Hexodine (Donyaye Behdasht), Chlorhexidine (Shahrdaru), Najo (Najo) and Behsa (Behsa) mouthrinses once a day for two minutes. The specimens were then immersed again in saliva. This process was repeated for two weeks. Color measurements were made on days seven and 14. Two-way and one-way ANOVA and Tukey's post hoc test, t-test and paired t-test were used to analyze data at a significance level of 0.05. Results: All specimens displayed color change after immersion in the mouthrinses. Significant interactions were found between the effects of materials and mouthrinses on color change. Conclusions: All composite resins tested showed acceptable color change after immersion in different mouthrinses. Filtek Z350XT showed less color change than Filtek Z250. Mouthrinses containing alcohol (Behsa and Najo) and citric acid (Vi-One) caused greater discoloration of composites. Keywords: Chlorhexidine; Color; Composite Resins; Mouthwashes